Prospects of conservative treatment for Clostridium septicum–associated aortitis - Patrick Kirchweger, MD; Helwig Wundsam, MD; Felix Bosse, MD; Alexander Kupferthaler, MD; Reinhold Huemer, MD; Reinhold Függer, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Clostridium septicum bacteremia is a rare (72 cases reported) aneurysm-inducing disease that has resulted in a 6-month mortality of 100% when treated conservatively. We report the case of a patient who was completely symptom free at 6 months of follow-up but who ultimately died at 8.9 months after aortic rupture. In compliance with the patient’s choice, a long-time antibiotic regimen was applied, instead of the surgical approach recommended by our surgical department. The use of an antibiotic regimen represents an option for patients unfit for surgery or as a bridge to surgery for damage control; however, aortic repair represents the only curative approach. Definitive antibiotic treatment is limited to a palliative approach for patients with C. septicum aortitis and has been accompanied by 100% 1-year mortality (90-day mortality, 84.2%).